Development and pilot of an advance care planning website for women with ovarian cancer: A randomized controlled trial - Vogel, Rachel Isaksson (Gynecol Oncol, 2013)
OBJECTIVE: Few available tools facilitate cancer patients and physicians' discussions of quality of life and end-of-life. Our objective was to develop a web-based tool to promote advance care planning for women with ovarian cancer. METHODS: Women with ovarian cancer, their families, clinicians and researchers met to identify ways to improve cancer care. A prototype website was created to address advance care planning, focusing on advance healthcare directives (AHD) and palliative care consultation. Patients were recruited from a gynecologic oncology clinic for a pilot randomized controlled trial. Primary outcomes included completion of an AHD and palliative care consultation. RESULTS: At study completion, 53 women with ovarian cancer were enrolled and 35 completed the study. The mean age at enrollment was 57.9 ± 9.5 years; most were newly diagnosed or at first recurrence. There were no statistical differences in completion of AHD (p = 0.220) or palliative care consultation (p = 0.440) between intervention and control groups. However, women in the intervention group showed evidence of moving toward decision making regarding AHD and palliative care and lower decisional conflict. Women assigned to the intervention, compared to control website, were highly satisfied with the amount (p = 0.054) and quality (p = 0.119) of information and when they accessed the website, used it longer (p = 0.049). Overall website use was lower than expected, resulting from several patient-related and design barriers. CONCLUSIONS: A website providing information and decisional support for women with ovarian cancer is feasible. Increasing frequency of website use requires future research.